PERLINDUNGAN HUKUM BAGI ANAK PENGIDAP HIV/AIDS MENURUT PERSPEKTIF HUKUM ISLAM - Dea Amilia Zanda; Qodariah Barkah; Armasito Armasito (Usroh: Jurnal Hukum Keluarga Islam, 2022)
HIV/AIDS is often associated with deadly diseases that are transmitted through promiscuity and homosexual behavior. HIV/AIDS is also said to be a cursed disease as a result of inappropriate behavior, so that it often creates stigma and discrimination against its sufferers which makes children with HIV/AIDS get bad treatment. This study aims to determine the perspective of Islamic law on legal protection for children with HIV/AIDS in Law Number 35 of 2014 concerning Child Protection. The research method used in this paper is a normative juridical method with the type of literature study. The results of this study show that legal protection for children with HIV/AIDS is in the form of special protection through surveillance, prevention, treatment, care, and rehabilitation efforts. Meanwhile, according to the perspective of Islamic law, protection of children with HIV/AIDS is a form of using maqashid shari'ah, which aims to protect children's self-esteem (hifz nafs) and provide peace in all aspects of social life. Keywords: Legal Protection; HIV/AIDS; Islamic Law